Study the effect of martensite-ferrite comstituents phase of the plain medium carbon dual phase (DP) steel on the mechanical property and corrosion behavior - Maisalsadila, Ismail (2017)
The investigation was carried out to study the effect of martensite-ferrite constituent phase on the medium carbon steels that undergo modified heat treatment process for three groups of samples and a group of untreated sample on corrosion test 1M hydrochloric acid. Each of the group samples were labeling with group A (untreated sample act as reference), B, C and D. The medium carbon steels for samples group C and D were heated to a temperature of 950 ˚C for completely austenite (y-phase) while samples group B were heated until temperature 750 ˚C to form ferrite-martensite dual phase region and then quenched in water. Then, group C and D steels were reheated until temperature 750 ˚C of ferrite-martensite dual phase region and rapidly quenched in water. Next, the steels were tempered at a temperature of 480 °C. The corrosion behavior of the carbon steel in 1M hydrochloric acid (HCL) was studied by measuring the weight loss of the steels. For untreated medium carbon steel, the weight loss is between 0.003g-0.022g while for heat treated medium carbon steel, the weight loss is between 0.004g-0.167g. The mechanical test was carried out on the samples of group A, B, C and D. The results obtained indicate that the specimen hardness is proportional to the amount of martensite in dual phase steel.